Ladies of Andijan Receive a Dignified Place in the History of State and Public Governance (Eurasian Journal of History, Geography and Economics, 2022)
The article focuses on the educated women of Andijan, who have a worthy place in the management of the state and society, are educated and have left an indelible mark on history with their multifaceted activities.